The General System of Royalties and implementation of a monitoring system, follow-up, control and evaluation of proceeds on account of the exploitation of non-renewable natural resources (2013)
This essay about the General System of Royalties presents the analysis of the advantages and weaknesses of the changes made to the system of royalties in Colombia especially in what corresponds to the implementation of a monitoring system, follow-up, control and evaluation of proceeds on account of the exploitation of non-renewable natural resources, since having an efficient and timely availability of information about the approved projects to be financed with resources of royalty, of progress in the implementation of these projects, the geographic location where the investment is carried out, the state of turns and the real-time execution of the resources, allows you to check the management right of the assignments made to local and regional authorities, as well as contributing to: that citizens have tools and actively participate in the overcoming of unmet basic needs of the population under their jurisdiction; that Government authorities take decisions according to the reality of the territorial entities and that the investments will increase according to provisions of macro fiscal policy and to comply with the standards of good governance.